Characterization And Properties Of Selected Biomass Nanofiller Reinforce Advanced Ceramic - Rajah, Siva Balan Rukumangatha (2014)

(untitled)
The aim of this study was to explore the carbon black nanofillers (CNF) from biomass and agricultural wastes as reinforcement material in ceramic application. Tujuan kajian ini adalah untuk meneroka karbon hitam daripada biojism pertanian dan sisa pertanian untuk menilai pengisi nano karbon (CNF) sebagai bahan dalam aplikasi seramik.